Living well to the end: A phenomenological analysis of life in extra care housing - Shaw, Rachel L. (Int J Qual Stud Health Well-being, 2016)
OBJECTIVES: To understand older adults’ experiences of moving into extra care housing which offers enrichment activities alongside social and healthcare support. DESIGN: A longitudinal study was conducted which adopted a phenomenological approach to data generation and analysis. METHODS: Semi-structured interviews were conducted in the first 18 months of living in extra care housing. Interpretative phenomenological analysis was used because its commitment to idiography enabled an in-depth analysis of the subjective lived experience of moving into extra care housing. Themes generated inductively were examined against an existential–phenomenological theory of well-being. RESULTS: Learning to live in an extra care community showed negotiating new relationships was not straightforward; maintaining friendships outside the community became more difficult as capacity declined. In springboard for opportunity/confinement, living in extra care provided new opportunities for social engagement and a restored sense of self. Over time horizons began to shrink as incapacities grew. Seeking care illustrated reticence to seek care, due to embarrassment and a sense of duty to one's partner. Becoming aged presented an ontological challenge. Nevertheless, some showed a readiness for death, a sense of homecoming. CONCLUSIONS: An authentic later life was possible but residents required emotional and social support to live through the transition and challenges of becoming aged. Enhancement activities boosted residents’ quality of life but the range of activities could be extended to cater better for quieter, smaller scale events within the community; volunteer activity facilitators could be used here. Peer mentoring may help build new relationships and opportunities for interactive stimulation. Acknowledging the importance of feeling—empathic imagination—in caregiving may help staff and residents relate better to each other, thus helping individuals to become ontologically secure and live well to the end.